2018
DOI: 10.1002/ccr3.1760
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally diagnosed large mediastinal lymphangioma: A case report

Abstract: Key Clinical MessageThoroughly planned labor with immediate postnatal resuscitation and percutaneous decompression is mandatory for a large mediastinal lymphangioma that compromises the cardiopulmonary function, and close observation with the administration of Eppikajutsuto (TJ‐28), a Japanese herbal medicine, may be a reasonable treatment, especially when resection of the lesion seems technically challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Up to date, no extensive research has been carried out on this subject. Several echocardiographic examinations in a fetus with lymphangioma allowed for the observation of the lesion and analysis of whether the lymphatic lesion affects cardiac function, e.g., due to compression or flow and cardiac output disturbances [8,23]. In addition, fetal heart echocardiography in the third trimester of pregnancy in a fetus with an extracardiac defect allows us to indicate the time, place, and manner of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, no extensive research has been carried out on this subject. Several echocardiographic examinations in a fetus with lymphangioma allowed for the observation of the lesion and analysis of whether the lymphatic lesion affects cardiac function, e.g., due to compression or flow and cardiac output disturbances [8,23]. In addition, fetal heart echocardiography in the third trimester of pregnancy in a fetus with an extracardiac defect allows us to indicate the time, place, and manner of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…They are observed in 1:6000 newborns at birth and in 1:750 spontaneous abortions. In the majority of cases, they involve the neck or axilla, but can also involve other parts of the body, such as: scrotum, retroperitoneum, gluteal region, mediastinum, groin, pelvis, mesentery, omentum and spleen [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The initial prenatal images raised the suspicion of pericardiac effusion, similar to the previously reported case. 4 Although mediastinal cLM is rare, it should be considered as a candidate in the differential diagnosis of fetal pericardiac effusion. Prenatal thoracocentesis caused shape changes of the target, which was an asymmetrical unilocular cystic lesion surrounding the heart.…”
Section: Discussionmentioning
confidence: 99%
“…7 Tanaka et al reported a case of neonatal respiratory distress due to mediastinal cLM requiring percutaneous decompression immediately after birth. 4 According to Jung et al, a mediastinal tumor can lead to lung hypoplasia and heart failure due to compression of the heart and the mediastinum. 7 After careful evaluation by MRI and sonography, prenatal percutaneous decompression could be considered for the prevention of fetal hydrops and lung hypoplasia, and emergent respiratory management just after birth could be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation